KINERJA KECEPATAN KENDARAAN PADA RUAS JALAN MENGGUNAKAN METODE PKJI 2014 DAN PORTABLE SPEEDGUN - Udi Subagyo; Achendri M. Kurniawan (Prokons: Jurnal Teknik Sipil, 2021)
Abstract The definite impact that will be caused by the increase in the number of transportation modes is traffic congestion. Jalan Soekarno – Hatta in front of the Polinema campus, is one of the roads in Malang City, which is quite strategically located because it connects the residential, educational and business areas, which are always crowded with vehicles every day. As a result of the volume of vehicles passing through the road is quite large and has a major effect on road performance (level of service) which can be measured based on the speed of vehicles crossing the road, a method is needed to facilitate vehicle speed measurement.. The method used to measure the performance (level of service) in the section is the measurement method with the Speedgun and PKJI 2014 where the expected goal of the results of this study is to obtain the performance of the road using the PKJI 2014 method, the performance of the road segment using a portable speed gun. and a comparison of road performance using the PKJI 2014 method and a portable speed gunThe results obtained from this study are the road segment performance (level of service) using the PKJI2014 method produces LOS (level of service) "E" with a light vehicle speed of 36.5 km/hour km/hour in the peak hour period 7.20-8.20, The performance of the speedgun measurement method produces an LOS (level of service) “E” with a light vehicle speed of 36 km/h km/h in the peak hour period 7.20-8.20 and the results of the comparison of the performance of the two methods is to produce LOS (level of service) “E ” where the measurement results of the PKJI 2014 method resulted in greater speed. Keywords: level of service, PKJI 2014, Speed Gun, comparison